2021
DOI: 10.1002/adsu.202100025
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4‐ethylenedioxythiophene) in Dye‐Sensitized Solar Cells: Toward Solid‐State and Platinum‐Free Photovoltaics

Abstract: Dye-sensitized solar cells (DSSCs) have become a strong reality in the field of hybrid photovoltaics. Their ability to operate in diffused light conditions and the possibility of fabrication of modules bearing different colors make these cells attractive for different applications, for example, wearable electronics, building integration, etc. This review focuses on one of the compounds rather often studied for DSSCs, namely, poly(3,4-ethylenedioxythiophene) (PEDOT). It has been introduced both as a substitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 316 publications
(411 reference statements)
0
38
0
Order By: Relevance
“…[99][100][101] Different dopants (e.g., PSS, tosylate, ClO 4 − , BF 4 − ) provide PEDOT with distinct electrical, mechanical, and electrochemical properties. [102][103][104][105][106] PEDOT-based conducting polymers show a tendency to adopt a lamellar stacking with alternating PEDOT and dopant layers. In PEDOT:PSS, due to the large size of the dopant anion and the resultant molecular stacking, the PEDOT chains adopt a coiled configuration with a benzoid structure.…”
Section: Poly(34-ethylenedioxythiophene) (Pedot) and Its Compositesmentioning
confidence: 99%
“…[99][100][101] Different dopants (e.g., PSS, tosylate, ClO 4 − , BF 4 − ) provide PEDOT with distinct electrical, mechanical, and electrochemical properties. [102][103][104][105][106] PEDOT-based conducting polymers show a tendency to adopt a lamellar stacking with alternating PEDOT and dopant layers. In PEDOT:PSS, due to the large size of the dopant anion and the resultant molecular stacking, the PEDOT chains adopt a coiled configuration with a benzoid structure.…”
Section: Poly(34-ethylenedioxythiophene) (Pedot) and Its Compositesmentioning
confidence: 99%
“…Moreover, the 3,4-substitution also lowers the oxidation potential at which thiophene-based monomers undergo polymerization [ 22 ]. Among them, the most studied polymer is poly(3,4-ethylenedioxythiophene) (PEDOT) [ 23 , 24 ], which is one of the most chemically stable conjugated polymers, demonstrating high conductivity in the doped state (3000 S/cm or more, which is only slightly lower than the conductivity of metals) [ 25 , 26 ]. PEDOT intermixed and stabilized by poly(styrenesulfonate) (PSS) is probably the most popular and widely used polymer mixture in the field of conducting polymers—PEDOT:PSS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fagiolari et al 2 outlined the application of poly(3,4-ethylenedioxythiophene) (PEDOT) as an ideal polymer organic conductor with excellent electrical conductivity, high flexibility, stability and low cost in the field of dye-sensitized solar cells (DSSCs). Beccatelli et al 3 demonstrated the functionalization of a commercial polyurethane (PU) foam with the conductive polymer PEDOT:PSS: the resulting material is a modified all-polymeric foam which can convert the material mechanical pressure into electrical signals.…”
Section: Introductionmentioning
confidence: 99%